2002
DOI: 10.1242/dev.00113
|View full text |Cite
|
Sign up to set email alerts
|

early in short days 4, a mutation inArabidopsisthat causes early flowering and reduces the mRNA abundance of the floral repressorFLC

Abstract: SUMMARYearly in short days 4, a mutation in Arabidopsis that causes early flowering and reduces the mRNA abundance of the floral repressor FLC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
114
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 70 publications
(128 reference statements)
3
114
0
Order By: Relevance
“…Transgenic esd4-1 mutants carrying 3C12 or 1E13 flowered at a similar time to the wild type and showed none of the pleiotropic phenotypes of esd4-1 (Figure 1) (Reeves et al, 2002). The region of overlap between 3C12 and 1E13 was predicted to encode at least two genes (At4g15870 and At4g15880; Figure 1A).…”
Section: Isolation Of Esd4 Suggests That It Encodes a Sumo-specific Pmentioning
confidence: 97%
See 2 more Smart Citations
“…Transgenic esd4-1 mutants carrying 3C12 or 1E13 flowered at a similar time to the wild type and showed none of the pleiotropic phenotypes of esd4-1 (Figure 1) (Reeves et al, 2002). The region of overlap between 3C12 and 1E13 was predicted to encode at least two genes (At4g15870 and At4g15880; Figure 1A).…”
Section: Isolation Of Esd4 Suggests That It Encodes a Sumo-specific Pmentioning
confidence: 97%
“…Previously, esd4-1 (Landsberg erecta [L er ]) was located to a 2-centimorgan interval on chromosome 4 between markers 326 and SC5 (Reeves et al, 2002). To increase the resolution of the esd4 map position, an additional 691 esd4-like F2 plants were screened with these markers, and ESD4 was located to a 35-kb region ( Figure 1A; see Methods) (Arabidopsis Genome Initiative, 2000).…”
Section: Isolation Of Esd4 Suggests That It Encodes a Sumo-specific Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, null alleles of flc completely suppress the late flowering caused by autonomous pathway mutations and active FRI alleles but have no effect on the delayed flowering in photoperiod pathway mutants ). Recently, it was shown that two other floral repressors, EARLY IN SHORT DAYS4 ( ESD4 ) and VERNALIZATION INDEPENDENCE4 ( VIP4 ), also act to maintain FLC levels (Reeves et al, 2002;Zhang and van Nocker, 2002). Therefore, FLC expression appears to be supported by genes such as FRI , VIP4 , and ESD4 and is repressed strongly by floral activators within the autonomous pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic A. thaliana plants, overexpression of SUMO1/2 caused increased global SUMOylation levels, attenuated the abscisic acid-mediated growth inhibition, and induced the expression of abscisic acid and stress-responsive genes, such as RD29A (Lois et al 2003). Dominant-negative A. thaliana mutants of the SUMOconjugating enzyme ESD4 yield plants that are smaller and show delayed flowering (Reeves et al 2002;Murtas et al 2003). A mutation in a putative SUMOylation attachment site of long after far red light 1 (LAF1), a transcriptional activator for phytochrome A signaling, alters LAF1 accumulation in the nucleus (Ballesteros et al 2001).…”
mentioning
confidence: 99%